(untitled) (Journal of Educational Sciences, 2019)
The article presents one of the results of scientific research related to the diagnostics of the motivational component of the future teachers’ training for integrated education in primary school. The purpose of the article is to substantiate the diagnostic tools for measuring the formation of the motivational component of the future teachers’ readiness for integrated education in primary school. The authors, referring to the regulatory documents, justify the relevance of the issue of teacher training for professional activities. The research methodology is presented on the basis of a theoretical analysis of modern scientific literature on this subject, a synthesis of psychological and pedagogical research in the field of training future primary school teachers for integrated learning. The study is organized on the basis of empirical methods: testing, questioning, observation, and conversation, mathematical and statistical methods of processing the obtained data. In addition, the authors of the study are guided by a system-activity approach. Guided by this approach, a complex of methods was selected. For the motivational component, a set of methods was selected and implemented to identify the level of readiness for professional activity: the method «Motives for choosing a profession» by the author R.V.Ovcharova; the technique «Diagnostics of the motivational sphere of the personality» by J.Newten; questionnaire «Barriers of teaching». The article notes that among the numerous methods of scientific and pedagogical research the most appropriate for determining the motivational component are questionnaires, which are indispensable for obtaining information about aptitudes, motives, opinions of the surveyed students. The analysis of the results of the motivational component of readiness is presented in detail. The reasons that influenced the learning outcomes of students of the specialty 5В010200 – «Pedagogy and methods of primary education» are described. The need for further work on the formation of the motivational component of training future teachers has been identified, which is facilitated by the subsequent implementation of the substantive and procedural components of the training future teachers for integrated primary school education. Key words: training, future teachers, integrated education, elementary school, ascertaining experiment.